Inversão do ônus da prova no processo penal brasileiro em face da criminalidade moderna: um estudo sobre a possibilidade do uso desse mecanismo de decisão no campo penal - Monnerat, Carlos Fonseca (2005)
The present study had as main objective, to examine the possibility of the use of the reversal of the burden of proof, applied to the Brazilian Criminal Process. The reversal of the burden of proof, rule destined mainly to aid the judge in his decision has been frequently used in the field of the consumer s right, authorized in the Brazilian Consumer Code. It allows that, as long as specific fundamentals are present, that the Judge can decide favorably to the weakest part in case that there is a doubt regarding the demonstration of the facts by the parts involved, not using the normal rule of distribution of the burden of proof, but the inversion of such distribution. As it is a rule of exception, it has to be clearly expressed. The questioning that is done is that considering the present characteristics of modern criminality, and the tendency to make some of the basic institutions and rules of the criminal law process more flexible, and in order to try to answer to the organized crime, that such instrument would be able to be used in this kind of legal process. The goal will be to provide the judge with a new rule to distribute the burden of proof, different of the usual in dubio pro reo. It comes as a fact that the modern criminality requires changes in the field of the criminal process. There are new theories worldwide in criminal law and its practical use, pointing to changes, some of them very extreme. It became necessary a detail exam of the truth, of the proof itself, of the criminal proof, of the burden of proof and of its inversion. With all these analyzed, it was realized that it will not be possible, considering the present Brazilian constitutional structure, to use the inversion of the burden of proof in the criminal process. To circumvent this, two legislative proposals were then formulated, one in the constitutional arena, and another in the area of the Brazilian Criminal Code. The first one to permit the reversion of the burden of proof in the practical determination of a criminal offense, after been established the certainty that the accused is part of a criminal organization. The second proposal, allowing the utilization of the reversal of the burden of proof considering the civil effects of the criminal sentence, with emphasis in the loss of property supposedly acquired with the product of a crime and which it was not proved that the acquisition was performed with unlawful proceeds.